1999
DOI: 10.1159/000029119
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunction at Baseline Predicts Symptomatic 1-Year Outcome in First-Episode Schizophrenics

Abstract: The present study addresses the consequences of cognitive disturbances on symptomatic outcome. Fifty-three first-episode schizophrenics were reassessed (n = 32) 1 year after admission. Simple regression analyses revealed that several self-perceived cognitive deficits at baseline as measured with the Frankfurt Complaint Questionnaire significantly predicted increased Brief Psychiatric Rating Scale global scores at follow-up (p = 0.05 to p = 0.005). A stepwise regression analysis proved memory dysfunction to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…The present study is in accordance with results from a prior investigation [6] showing that subjective dysfunction is a significant predictor of later psychopathology. Again, subjective cognitive dysfunction strongly correlated with outcome.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The present study is in accordance with results from a prior investigation [6] showing that subjective dysfunction is a significant predictor of later psychopathology. Again, subjective cognitive dysfunction strongly correlated with outcome.…”
supporting
confidence: 93%
“…A review compiled by Green [4] as well as subsequent research [5] has indicated that (objective) neurocognitive deficits are predictors of the functional outcome such as independent living and interpersonal relations. In a recent study, we were able to show that the 1-year symptomatic outcome assessed by Brief Psychiatric Rating Scale was significantly correlated with subjective cognitive and perceptual complaints on admission in first-episode patients [6]. Subjective cognitive dysfunction was determined using the Frankfurt Complaint Questionnaire (FCQ) [7], a self-report questionnaire predominantly comprising perceptual and cognitive deficits.…”
mentioning
confidence: 99%
“…Cognitive deficits in memory, executive function, and working memory are believed to be of major importance to the functional and symptomatic outcome (Fujii and Wylie, 2003;Moritz et al, 2000;Grawe and Levander, 2001;Green et al, 2000) as well as the quality of life (Fujii et al, 2004) of patients with schizophrenia. Being able to address some of these symptoms in a preclinical model and consequently develop drugs that better target these symptoms could lead to better outcome and better quality of life for the patients.…”
Section: Introductionmentioning
confidence: 99%
“…In one study applying the method proposed by Liddle and Morris [12] of a tri­partite distinction between psychomotor poverty, disorganization and reality distortion, disorganization showed the most reliable relationship to community functioning [13]. Further studies were able to demonstrate an association between cognitive impairment and poor symp­tomatic outcome [14−16]. These findings suggest that both cognitive impairment and symptom level may play a role as ‘rate‐limiting factors’.…”
mentioning
confidence: 99%